The Influence of Iron Tablet Supplementation and Red Guava Juice on Hemoglobin Level Increase Among Female Students at SMK N 3 Kintamani Bangli - Ni Ketut Aryandani; Ida Ayu Eka Padmiari; I Wayan Ambartana (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Based on the 2018 Riskesdas data, the prevalence of anemia in adolescent girls aged 5-14 years is 26.8%. Anemia prevention can be done through iron supplement tablets and foods rich in vitamin C. SMKN 3 Kintamani regularly receives iron supplement tablets, but students often do not consume them regularly. This study aimed to examine the effect of iron supplement tablets and red guava juice on hemoglobin levels in adolescent girls at SMKN 3 Kintamani. Using a quasiexperimental design with two groups, the research was conducted in March-April 2024 on 10th-grade students. The results showed that there was an effect of giving iron supplement tablets and red guava juice on hemoglobin levels before and after the intervention in the treatment group with a p-value of 0.001. There was also an effect of giving iron supplement tablets and red dragon fruit juice on hemoglobin levels before and after the intervention in the control group, with a p-value of 0.001. Both groups showed a significant increase, but the treatment group had a greater rise in hemoglobin levels than the control group. It is recommended that adolescent girls regularly consume iron supplement tablets and foods rich in iron and vitamin C to prevent anemia.